2019
DOI: 10.3390/data4040143
|View full text |Cite
|
Sign up to set email alerts
|

Land Cover Mapping using Digital Earth Australia

Abstract: This study establishes the use of the Earth Observation Data for Ecosystem Monitoring (EODESM) to generate land cover and change classifications based on the United Nations Food and Agriculture Organisation (FAO) Land Cover Classification System (LCCS) and environmental variables (EVs) available within, or accessible from, Geoscience Australia’s (GA) Digital Earth Australia (DEA). Classifications representing the LCCS Level 3 taxonomy (8 categories representing semi-(natural) and/or cultivated/managed vegetati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…To overcome the issue of national yearly land cover maps, a valuable solution can be the use of the Earth Observation Data for Ecosystem Monitoring (EODESM) model (Lucas & Mitchell, 2017;Lucas, Mitchell, Manakos, & Blonda, 2018). It is currently under implementation in Digital Earth Australia (Lucas et al, 2019). This model facilitates regular classification according to the Food and Agricultural Organization -Land Cover Classification System (FAO -LCCS) as well as translations to other taxonomies like the General Habitat Classification.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the issue of national yearly land cover maps, a valuable solution can be the use of the Earth Observation Data for Ecosystem Monitoring (EODESM) model (Lucas & Mitchell, 2017;Lucas, Mitchell, Manakos, & Blonda, 2018). It is currently under implementation in Digital Earth Australia (Lucas et al, 2019). This model facilitates regular classification according to the Food and Agricultural Organization -Land Cover Classification System (FAO -LCCS) as well as translations to other taxonomies like the General Habitat Classification.…”
Section: Discussionmentioning
confidence: 99%
“…21), Geoscience Australia is leading an inter-institutional initiative to produce reliable, standardized, continental-scale maps of land cover and land-cover dynamics across Australia at 25 m spatial resolution using multi-scale time series of Landsat and Copernicus Sentinel datasets. This approach builds on the Earth Observation Data for Ecosystem Monitoring (EODESM; Lucas and Mitchell 2017), which is fully described in Lucas et al (2019a) and which provides multi-scale and temporal land-cover and evidence-based change maps by integrating environmental variables retrieved from EO data and utilizing the framework of the Food and Agriculture Organisation (FAO) Land Cover Classification System (LCCS; Version 2, Di Gregorio 2016). The approach is based on the requirement for information about land cover and its change over time, as both are essential input metrics to several SDG targets (Fig.…”
Section: Case Study Of Australia: Operationalizing the Indicator Frammentioning
confidence: 99%
“…The DEA land cover product has been optimized for high-performance computing within the Open Data Cube (ODC) framework and is generating continental maps of land-cover datasets from environmental variables (thematic and continuous), with a focus on those that are generated at a national level within DEA's ODC environment (Lucas et al 2019a) and for multiple points in time. These include the vegetation cover fraction of the Joint Remote Sensing Research Program (Gill et al 2017), Water Observations from Space (WOfS) (Mueller et al 2016), surface reflectance Median Absolute Deviation (MAD) (Roberts et al 2018), and national mangrove distribution (Lymburner et al 2019) (Fig.…”
Section: Dea To Map Land Cover and Dynamics Over Timementioning
confidence: 99%
See 1 more Smart Citation
“…Poussin et al [42] demonstrated the benefits of Open and Reproducible Science using a snow detection algorithm, developed in Switzerland and shared as an open notebook, to monitor snow cover evolution for the last three decades in the Gran Paradiso National Park in Italy. Furthermore, Lucas et al [43] developed a conceptual framework to implement a Land Cover Change model, providing Australia and other countries using the Open Data Cube (ODC) environment with the opportunity to routinely generate land cover maps from Landsat or Sentinel-1/2 data, at least annually and using a consistent and internationally recognized taxonomy.…”
mentioning
confidence: 99%